CRITERIA AND INDICATORS OF INTELLECTUAL MOBILITY OF FUTURE ENGINEERS IN EDUCATIONAL ENVIRONMENT OF A TECHNICAL UNIVERSITY - Міхненко, Г. Е. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2015)
The article is devoted to the consideration and analysis of the criteria and indicators of intellectual mobility of future engineers in educational environment of a technical university. The author defines the following criteria and indicators: motivational (understanding of significance of intellectual development, interest in intellectual activity); cognitive (characteristics of thinking; level of mental functions; creativity); operational and technological (instrumental competencies; ability to use cognitive strategies); metacognitive (awarenessof intellectual mobility issues and personal psychological characteristics; self-regulation of intellectual activities; self-criticism); personality and social(manifestation of adaptability, communicativeness, tolerance, persistence in achieving goals)